ANALISIS OPTIMALISASI MOBILE VILLAGE LEARNING CLASS DALAM MENGATASI DISPARITAS IMPLEMENTASI KURIKULUM DI SD WILAYAH 3T - Aisyah, Putri; Mutmainah, Siti; Novella, Yasfi; Alya Mastura, Nafisa; Ilma, Khairi; Thaariq Fikri, Ath; Candra; M. Habibi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The disparity of curriculum implementation in elementary school located in frontier, outermost, and disadvangated (3T) areas remains a major challenge in achieving equitable education in Indonesia. Limited educational facilities, uneven teacher distribution, and difficult geographical access contribute to ineffective learning processes and suboptimal curriculum delivery. This study aims to analyze the role of Mobile Village Learning Class (MOVICLASS) as an innovative mobole learning system designed to support curriculum implementation in 3T elementary schools. The study employed a descriptive qualitative approach through a case study method bt examining educational phenomena in several 3T regions using literature studies, eduacational reports, and contectual analysis. The findings indicate that MOVICLASS flexible learning environment through mobile educational services, collaborative teaching systems, amd community-based learning activities. In addition, this innovation contributes to improving curriculum accessibility, strengthening learning effectiveness, and supporting equitable educational services for elementary school students in remote areas. Therefore, MOVICLASS in considered a relevant alternative strategy in supporting inclusive and sustainable education development in Indonesia's 3T religions.